Impacto geotécnico de los derrames de diésel en suelos finos (2017)
Currently the growth of the world population has led to increased consumption of oil and its derivatives, which have become massive refineries, transport networks, storage facilities and fuel sales all increase the likelihood of spills. These effusions hydrocarbons generated by gravity and capillary forces to move vertically and horizontally through different soil layers. Then the question arises: ¿what happens in the geotechnical properties and the mineralogical composition of the fine soils when it is contaminated of diesel? It is a question that many authors have realized in the world but that needs to continue the line of research, in the case of Colombia area a few investigations. The research centred on studying four (4) types of fine soils which corresponded to clays, and methodology of experimentation was based on an exploratory phase and subsequently, the experimental phase carried out based on the literature review where was allowed a time of exposition to hydrocarbon of one week. Diesel was chosen as hydrocarbon because it is the main fuel that is handled in Colombia and have the lowest risks of manipulation in the laboratory. To give answer the research question involved the realization the laboratory tests to determine moisture content, specific gravity of solids, Atterberg limits, resistance to unconfined compression and analysis of mineralogy with X-ray diffraction (XRD), method of dust, of the control samples and samples with treatment of 1%, 3% and 6% of diesel with respect to the dry weight of the samples. The results of the research have shown the uncertainty in the geotechnical properties of the soils used in experimentation by the interaction that they had with diesel. The moisture content increase, although the expression of its calculation is questionable; the specific gravity of the solids and the resistance to unconfined compression decreased; and the Atterberg limits have an indefinite behavior due to the presence of diesel and it is calculated as a moisture content. The mineralogical composition and classification (USCS) of the experimental units were not affected by the presence of diesel. In brief, this research found changes in the geotechnical properties of the experimental units with presence of diesel, and let the approach of future research based on the results obtained.